2013
DOI: 10.5750/ejpch.v1i2.688
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating person-centered medicine in future physicians

Abstract: Person-centered medicine, while valued implicitly, is not always taught explicitly in medical schools or during residency programs. Threats to educating and practicing person-centered medicine include perceived lack of time, stress, burnout and a paucity of mentors with a systematic approach to modeling and teaching students how to relate to patients in a way that addresses them as whole persons. Herein we review how trainee stress and burnout negatively impact patient care and outline a program designed to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 36 publications
0
54
1
6
Order By: Relevance
“…Similar to the results of Hallberg [50], a study of Swedish district nurses showed no impact of clinical supervision on burnout [143]. While Morrison Wylde et al [70] found a marginal improvement in pediatric nurse burnout with smartphonebased intervention vs. traditional mindfulness interventions, studies investigating mindfulness interventions in other healthcare populations reported mixed results [144][145][146][147]. Similar to pediatric nurses [84], social workers showed a significant decrease in burnout after attending skills development courses [148] suggesting that improving clinical knowledge and skills may reduce burnout.…”
Section: Interventionsmentioning
confidence: 68%
“…Similar to the results of Hallberg [50], a study of Swedish district nurses showed no impact of clinical supervision on burnout [143]. While Morrison Wylde et al [70] found a marginal improvement in pediatric nurse burnout with smartphonebased intervention vs. traditional mindfulness interventions, studies investigating mindfulness interventions in other healthcare populations reported mixed results [144][145][146][147]. Similar to pediatric nurses [84], social workers showed a significant decrease in burnout after attending skills development courses [148] suggesting that improving clinical knowledge and skills may reduce burnout.…”
Section: Interventionsmentioning
confidence: 68%
“…Of the various approaches reported, Mindfulness-Based Stress Reduction has been shown to improve medical students' well-being by decreasing levels of stress and depression, and increasing empathy and self-compassion. [8][9][10] However, bearing in mind the circles within circles proposed in this commentary, although students may be encour-aged to engage in self-care and to practise medicine mindfully, they are unlikely to practise what they have learned if they are in a medical context that either fails to encourage this or, worse, extinguishes it.…”
Section: Patricia L Dobkin and Samantha Balassmentioning
confidence: 98%
“…El impacto del estrés y de este síndrome en la salud física de los profesionales ha sido documentado en numerosos estudios (32). Por otro lado, se ha mostrado que el estrés disminuye significativamente la atención, la concentración y la habilidad de tomar decisiones (33). Los síntomas pueden llevar al médico a cometer errores que a su vez contribuyen a que el burnout aumente; y dados los costos potenciales de estos errores médicos, su impacto emocional puede ser devastador para los profesionales de la salud (32).…”
Section: La Atención Espiritual En Los Cuidados Paliativosunclassified